Research on the Digital Application of Museums under AIGC Technology - Chen, Xiaotong (Journal of Theory and Practice of Management Science, 2025)
With the rapid development of artificial intelligence technology, AIGC technology has become an important force in promoting the digital transformation of museums. This article explores the practice and impact of AIGC (Artificial Intelligence Generated Content) technology in the digital application of museums. Analyze the current application status of AIGC technology in museums, including cultural relic identification and appreciation, smart museum construction, and cultural and creative product design. Identify the issues in the application of AIGC technology, such as data quality and bias, balance between cultural heritage and innovation, and ethical and legal risks. In response to these issues, this article further explores corresponding countermeasures, including improving data quality, promoting cultural inheritance and innovation, and strategies to address ethical and legal risks. It emphasizes that while enjoying the convenience brought by technology, attention should also be paid to the depth and breadth of technological applications to realize the core values of museum research and inheritance.